Soil conservation and water conservation services and trade-offs following the land consolidation project: a case study of Yan’an city, China - Jing, Wang; Yang, Zhang; Longfei, Xia; Jianfeng, Li; Huan, He; Siqi, Liu (Frontiers in Environmental Science, 2024)
The Loess Plateau is an important region for soil and water conservation and ecological construction in China. Exploring the spatio-temporal variations in soil conservation and water conservation services and their relationships in Loess Plateau under the background of land consolidation projects is of great significance for ecological protection and quality development in the Yellow River Basin.Taking Yan 'an city as the research area, this paper used the InVEST model to quantitatively evaluated spatio-temporal variation characteristics and trade-off/synergy relationship of the soil conservation and water conservation services from 2010 to 2018. According to the implementation data, the relationship between the gully control and land consolidation(GCLC) project in various counties of Yan 'an city and soil conservation and water conservation service was analyzed. The results showed that the total amount of soil conservation services in Yan 'an City were 4.07×10 6 t and 3.75×10 6 t in 2010 and 2018 with a decrease of 7.76%, and with low spatial clustering characteristic. The total amount of water conservation services were 2.01×10 10 mm and 2.03× 10 10 mm in 2010 and 2018 with a increase of 0.56%, and with high spatial clustering characteristic.There is a synergistic relationship between soil conservation and water conservation services in most area of Yan 'an city. From 2010 to 2018, the effect of the GCLC projects on soil conservation and water conservation services in Yan'an city is not significant.